Highly spin-polarized carbon-based spinterfaces. (June 2015) - Djeghloul, F.; Garreau, G.; Gruber, M.; Joly, L.; Boukari, S.; Arabski, J.; Bulou, H.; Scheurer, F.; Hallal, A.; Bertran, F.; Le Fèvre, P.; Taleb-Ibrahimi, A.; et al.
Abstract: We deploy topographical and spectroscopic techniques to show that a strongly spin-polarized interface arises between ferromagnetic cobalt and an amorphous carbon layer. Scanning tunneling microscopy and spectroscopy show how a semiconducting carbon film with a low band gap of about 0.4 eV is formed atop the metallic interface. To understand how the cobalt/carbon interface is formed, we used X-ray photoemission spectroscopy to study the hybridization state of carbon. We find that the semiconducting layer consists mainly of sp 2 -bonded carbon atoms with a sp 2 -to-sp 3 ratio between 1.4 and 1.8. The spin-polarized properties of the cobalt/carbon interface are studied by spin-resolved photoemission spectroscopy. We observe interface states close to the Fermi energy that are not exclusive to cobalt. These electronic states reveal a high degree of spin polarization at room temperature.